How to train your dragon : the chapter book - Bright, J. E. (New York : HarperFestival, 2010)
Chronicles the adventures and misadventures of Hiccup Horrendous Haddock the Third as he tries to pass the important initiation test of his Viking clan, the Tribe of the Hairy Hooligans, by catching and training a dragon.
Film tie-in.
Keywords: Haddock, Hiccup Horrendous, III (Fictitious character) -- Juvenile fiction; Vikings -- Juvenile fiction; Dragons -- Juvenile fiction; Initiation rites -- Juvenile fiction; Film novelizations -- Juvenile fiction; Adventure stories -- Juvenile fiction; Historical fiction -- Juvenile fiction